Effect of Natural Growth Regulators from Banana Corm Filtrate and Mung Bean Sprouts on The Viability and Vigor of Tomato Seeds (Solanum Lycopersicum L.) - Nabilah, Sulthanah; Dewi, Sari Kusuma (Journal of Authentic Research, 2026)
Tomato seeds (Solanum lycopersicum L.) that have passed their expiration date generally exhibit reduced viability and quality. Seed quality can be improved through invigorization using natural plant growth regulators (PGRs) derived from banana corms and mung bean sprouts, which contain hormones such as auxins, gibberellins, and cytokinins that stimulate the germination of expired seeds. This study aimed to determine the effect of concentration and type filtrate (banana corm and mung bean sprout) as natural PGRs, as well as their interaction, on the viability and vigor of expired tomato seeds. The study employed a Randomized Complete Block Design (RCBD) with two factors: filtrate concentration (0%, 20%, 40%, 60%, and 80%) and filtrate type (banana corm and mung bean sprout), with three replications. The observed parameters included seed viability (germination percentage) and vigor (vigor index, germination speed, and uniformity of growth). The results showed that both concentration and type filtrate of had a significant effect on all observed parameters. The best treatment was obtained from the combination of banana corm and mung bean sprout filtrates at a concentration of 60% and combination of banana corm and mung bean sprout filtrates at a concentration of 80%, which significantly enhanced the viability and vigor of the seeds compared to other treatments. Furthermore, the interaction between filtrate concentration and type had a significant effect on all parameters, including germination percentage.